Replication of the Reticuloendotheliosis Virus (Strain T) in Chicken Embryo Cell Culture - Bose, Henry R. (1967)
Investigations were conducted on the in vitro replication of the reticuloendotheliosis (RE) virus (strain T) in specific-pathogen-free chicken embryo fibroblast (CEF) cultures. Active virus production was detected in the tissue culture fluid 24 hr after infection. When injected into chickens, samples taken 42 hr after infection of the cell cultures killed approximately 50% of the birds at a 1:100 dilution. The RE virus titer remained at this level for 5 days before declining. Cell-free virus preparations from tissue cultures rarely resulted in 100% mortality of the assay birds. The level of cell-associated virus was very low. Evidence that the reticuloendotheliosis was not induced by a mycoplasma was indicated by failure to isolate an organism on PPLO Agar (Difco) and failure of kanamycin or amphotericin B to inhibit multiplication of RE virus in vitro. RE virus appeared to be unrelated to members of the avian leukosis and sarcoma complex. It did not induce resistance in CEF cultures to sarcoma viruses of the A or B subgroup of this complex. Similarly, preinfection of cell cultures with leukosis viruses of the A or B subgroup did not inhibit or reduce the replication of RE virus.